Interstitial light-trapping design for multi-junction solar cells - Mellor,AV; Hylton,N; Maier,S; Ekins-Daukes,N (Solar Energy Materials and Solar Cells, 2016)
We present a light-trapping design capable of significantly enhancing the photon absorption inany subcell of a multi-junction solar cell. The design works by coupling incident light intowaveguide modes in one of the subcells via a diffraction grating, and preventing these modesfrom leaking into lower subcells via a low-index layer and a distributed Bragg reflector, whichtogether form an omnidirectional mirror. This allows the thickness of the target subcell to bereduced without compromising photon absorption, which improves carrier collection, andtherefore photocurrent. The paper focuses on using the composite structure to improve theradiation hardness of a InGaP/Ga(In)As/Ge space solar cell. In this context, it is shown viasimulation that the Ga(In)As middle-cell thickness can be reduced from 3500 to 700 nm,whilst maintaining strong photon absorption, and that this leads to a significantly improvedend-of-life photocurrent in the Ga(In)As middle cell. However, the design can in general beapplied to a wide range of multi-junction solar cell types. We discuss the principles ofoperation of the design, as well as possible methods of its fabrication and integration intomulti-junction solar cells.